Blurring ontological boundaries: The transactional nature of material engagement. (April 2023) - Alessandroni, Nicolás; Malafouris, Lambros
The target article provides valuable reflections regarding the study of cognition-in-the-world and proposes a methodology that could help researchers unravel the structure and temporal unfolding of lived experience. In this commentary, we discuss the authors' commitment to the enactive notion of sense-making as the activity of an autonomous system that brings forth a meaningful world to maintain its self-constituted identity. From Material Engagement Theory, we hold that defending such a notion leads to unnecessary ontological asymmetries that obscure the fundamental role of materiality for cognition. On the one hand, we argue that the relationship of close intertwinement and co-constitution that unites organism and environment makes it untenable to characterise cognition as being driven by individuals. In our view, cognition arises from the dynamic encounter between brains, bodies and culture. On the other hand, we suggest that organism and environment should not be seen as separate ontological categories that come to interact with each other but as two terms of a transactional process of continuous becoming. Consistently, we propose to consider meaning as emerging from the in-between space that material engagement creates rather than from the activity of an organism.